The Distributional Impacts of Energy Taxes. (31st January 2019) - Pizer, William A; Sexton, Steven
Abstract: Taxes have long been advocated by economists for efficient pollution control, particularly in the energy sector. However, these taxes may enjoy less political support than standards-based regulation at least partly because of the common assumption that they place a greater burden on the poor than the rich. This article evaluates the validity of that assumption by reviewing the literature on the distributional impacts of energy taxes and by analyzing energy consumption surveys in select countries. The evidence suggests that energy taxes need not be as regressive as is often assumed. We find that the incidence (i.e., distributional impact) of such taxes depends upon the energy commodities that are taxed; the physical, social, and climatic characteristics of the jurisdictions in which they are implemented; and the use of energy tax revenues. We also show that the variation in household energy expenditure is greater within income groups than across income groups and that such variation is not easily reduced.